Wybrane formy oddziaływań duchowych jako alternatywa dla tradycyjnych form terapii osób cierpiących z powodu uzależnień - Hoffmann, Beata; Motyka, Marek Adam (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The article presents the role of spiritual interventions offered to people suffering from drug addiction in selected institutions in Poland. Pioneering interventions aimed at existential support for patients, both in Poland and in other places in the world, are presented. Attention is paid to the possibilities resulting from taking care for the stabilisation of the spiritual sphere devastated by addiction. Examples of the activities of institutions offering care for this important dimension for those struggling with addiction as part of therapeutic and rehabilitation services are given. Addicts repeatedly make unsuccessful attempts to change their life situation. For many of them, these institutions could be an important alternative in their current struggles. For people who profess religious values, they could be an additional source of reinforcement or motivation to undertake the treatment process.